2022
DOI: 10.1177/03611981221108150
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Influence Factors in Crashes Alongside an Intersection Using a Multinomial Logit Approach

Abstract: Traffic violations are the leading cause of fatalities and injuries, and current trends indicate that this will proceed in the foreseeable future, especially alongside intersections. This study aims to examine the determinants of crash influencing factors alongside intersections using unweighted data points collected from the Michigan counties of Wayne, Genesee, and Macomb. Firstly, the random forest method identifies the significant predictor variables. Meanwhile, six predictor variables are considered: the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The increase in crash frequency at the higher posted speed limit is expected since increased speeds are known to entail a higher risk of a crash. In that regard, several studies have demonstrated the positive exponential relationship between the speed limit and crashes ( 37 , 6870 ). In alignment with this study, the previous study of Alhomaidat et al ( 71 ) indicated a 13.9 percent increase in arterial road crash frequency as a result of 5 mph increase in adjacent freeway speed limits.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in crash frequency at the higher posted speed limit is expected since increased speeds are known to entail a higher risk of a crash. In that regard, several studies have demonstrated the positive exponential relationship between the speed limit and crashes ( 37 , 6870 ). In alignment with this study, the previous study of Alhomaidat et al ( 71 ) indicated a 13.9 percent increase in arterial road crash frequency as a result of 5 mph increase in adjacent freeway speed limits.…”
Section: Discussionmentioning
confidence: 99%
“…An important assumption in classic multinomial logit (MNL) models is the compensatory behavior of decision-makers, implying a decision strategy that permits exchange or variation between attribute values to maintain a fixed level of utility [19,20]. These models, however, do not accommodate thresholds or limits on attributes, such as price, and typically overlook the impact of product shortages or competition among consumers for limited units.…”
Section: Literature Reviewmentioning
confidence: 99%